Analisis Dampak dan Kontroversi Penerapan Perda Syariat di Indonesia: Studi Kasus Aceh: (Studi Kasus di Provinsi Aceh) - Parawati, Erina Dwi; Muhaimin (Pascasarjana Universitas Al-Qolam Malang, 2025)
The phenomenon of implementing Regional Regulations (Perda) based on Sharia in several regions of Indonesia has sparked various public reactions, particularly because these regulations are seen as local efforts to preserve Islamic values amidst the currents of modernization and globalization. This policy emerged alongside the introduction of regional autonomy in 1999, which granted greater authority to regional governments to govern their areas in line with the aspirations of local communities. Aceh stands out as a region with special rights to implement Sharia law through Law No. 11 of 2006. This phenomenon has given rise to diverse views and debates, from supporters who view Sharia regulations as an effort to uphold public morality, to critics who argue that these rules may discriminate against minority groups. This study aims to analyze the impacts, challenges, and controversies related to the implementation of Sharia-based regional regulations in Indonesia, particularly in Aceh. Using qualitative analysis methods, this research examines public perceptions of these regulations, their effectiveness, and their legal implications on citizens' fundamental rights. The findings indicate that, while Sharia regulations can create social order aligned with the norms of the majority, they also face challenges in terms of inconsistent law enforcement and potential conflicts with human rights principles, especially for non-Muslim communities.